1992
DOI: 10.1111/j.1600-0447.1992.tb03259.x
|View full text |Cite
|
Sign up to set email alerts
|

The Parental Bonding Instrument in adolescent patients with anorexia nervosa

Abstract: The Parental Bonding Instrument (PBI) was administered to 54 adolescent patients with anorexia nervosa. Scores were compared with those of matched groups of normal and of nonanorectic adolescents referred for assessment to an adolescent psychiatric unit. Significant differences between the 3 groups were demonstrated with respect to care and protection dimensions. Overall scores of subjects in the anorectic group resembled those of normals rather than those of referred patients. Anorexia nervosa patients descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 10 publications
3
33
3
Order By: Relevance
“…A study involving Chinese parents in Taiwan and the United States suggested that a more democratic parenting style was associated with higher BMI (Chen and Kennedy, 2004). While other studies have shown that democratic parenting was associated with better health in children (Russell et al, 1992;Hill and Franklin, 1998), which was consistent with our results. A parent's expression of nurturing emotion with clear communication and realistic behavioral expectations is imperative to a child's development and healthy behavior, as it provides motivation for a child, allows the parent to help establish healthy behaviors and reinforces self-regulation, thereby allowing the child to develop new and healthy activities (Goetz and Caron, 1999).…”
Section: Discussionsupporting
confidence: 83%
“…A study involving Chinese parents in Taiwan and the United States suggested that a more democratic parenting style was associated with higher BMI (Chen and Kennedy, 2004). While other studies have shown that democratic parenting was associated with better health in children (Russell et al, 1992;Hill and Franklin, 1998), which was consistent with our results. A parent's expression of nurturing emotion with clear communication and realistic behavioral expectations is imperative to a child's development and healthy behavior, as it provides motivation for a child, allows the parent to help establish healthy behaviors and reinforces self-regulation, thereby allowing the child to develop new and healthy activities (Goetz and Caron, 1999).…”
Section: Discussionsupporting
confidence: 83%
“…Parenting styles (warmth and control) have been viewed as very important in understanding the mental health of children and parents as well as childhood personality development [1][2][3][4][5][6][7][8][9][10][11][12] and the onset of mental illnesses in adulthood [13][14][15][16][17][18][19]. Parents' rearing behaviours are similar to those experienced by their own parents when they were children.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of anorectic patients presented higher scores in the care factor and lower scores in overprotection when compared with a control group (30).…”
Section: Introductionmentioning
confidence: 77%